Immune Control by TRAF6-Mediated Pathways of Epithelial Cells in the EIME (Epithelial Immune Microenvironment) - Dainichi, Teruki; Matsumoto, Reiko; Mostafa, Alshimaa; Kabashima, Kenji (Frontiers in Immunology, 2019)
In the protective responses of epithelial tissues, not only immune cells but also non-immune cells directly respond to external agents. Epithelial cells can be involved in the organization of immune responses through two phases. First, the exogenous harmful agents trigger the primary responses of the epithelial cells leading to various types of immune cell activation. Second, cytokines produced by the immune cells that are activated directly by the external agents and indirectly by the epithelial cell products elicit the secondary responses giving rise to further propagation of immune responses. TRAF6 is a ubiquitin E3 ligase, which intermediates between various types of receptors for exogenous agents or endogenous mediators and activation of subsequent transcriptional responses via NF-kappaB and MAPK pathways. TRAF6 ubiquitously participates in many protective responses in immune and non-immune cells. Particularly, epithelial TRAF6 has an essential role in the primary and secondary responses via driving type 17 response in psoriatic inflammation of the skin. Consistently, many psoriasis susceptibility genes encode the TRAF6 signaling players, such as ACT1 (TRAF3IP2), A20 (TNFAIP3), ABIN1 (TNIP1), IL-36Ra (IL36RN), IkappaBzeta (NFKBIZ), and CARD14. Herein, we describe the principal functions of TRAF6, especially in terms of positive and regulatory immune controls by interaction between immune cells and epithelial cells. In addition, we discuss how TRAF6 in the epithelial cells can organize the differentiation of immune responses and drive inflammatory loops in the epithelial immune microenvironment, which is termed EIME.